Leçons de Tenebrae: Brian Cherney, Paul Celan, and a Music of Witness - Vishio, Anton (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2017)
In several compositions, Brian Cherney has reflected on the Holocaust and its impact, exploring how music can respond to such tragedy; his recent engagement with the poetry of Paul Celan is a natural extension of these preoccupations. This article offers a close reading of Cherney’s choral setting of Celan’s Tenebrae. The composer incorporates several additional texts that create a genealogy of the poem, from biblical passages to fragments of Dante and Hölderlin to accounts of the Holocaust itself; he arranges these texts to highlight semantic and sonic features of Celan’s work. Perhaps Cherney’s boldest move is his insertion of Hebrew letters, linking his composition to the long tradition of Lamentations settings—a link cemented by a quotation from Couperin’s Leçons de Ténèbres, which provides important motivic material. Through these additions, Cherney turns the poem towards us, inviting us to respond to its call for reflective witness.